Chemical aspects of the application of basalt in cement composites. (3rd October 2022) - Scheinherrová, Lenka; Keppert, Martin; Černý, Robert
Highlights: Overview of main applications of basalt in cement composites is presented. Chemical interactions of basalt with corrosive environments are described. Chemical reactivity of various forms of basalt in cementitious matrices is assessed. Gaps in the current knowledge are identified. Suggestions for future research are formulated. Abstract: Basalt belongs to materials widely used in engineering. Basalt-based products are common in civil engineering, automotive, or boat building, but they can be found, e.g., also in wind turbine blades or sporting goods. This paper is focused on the chemical aspects of the application of basalt in cement composites, a seemingly narrow area that was not surveyed in sufficient detail to date. At first, an overview of the main applications of basalt in cement composites is presented. The effects of active fillers, coarse aggregates, and various types of reinforcement on functional properties are analyzed using a set of characteristic examples. Then, the chemical reactivity of various forms of basalt in cementitious matrices is assessed. Mechanisms of chemical interactions of basalt with corrosive environments are described on a general level to provide a guide for such assessment. Consequently, the interactions of basalt in powdered or aggregate form and basalt reinforcement with the cement matrix are specified from a chemical point of view. Finally, suggestions for future research inspired by the revealed gaps in the current knowledge are formulated.